The Effect of Discipline on Employee Productivity at PT. Cipta Selaras in Pamulang - Bagus Kuncoro Indarto; Umi Rusilowati (Kontigensi : Jurnal Ilmiah Manajemen, 2021)
This study aims to determine the effect of discipline on employee productivity at PT. Cipta Selaras in Pamulang. The method used is explanatory research with a sample of 56 respondents. The analysis technique uses statistical analysis with regression, correlation, determination and hypothesis testing. The results of this study of the discipline variable obtained an average score of 3.748 with suitable criteria. Employee productivity variable obtained an average score of 3.868 with suitable criteria. Discipline has a positive and significant effect on employee productivity with a regression equation value of Y = 14.665 + 0.641X, and a correlation coefficient value of 0.766 has a strong relationship with a determination value of 58.7%. Hypothesis testing obtained a significance of 0.000 < 0.05. abstracts are typed in single spaces.